Copper segregation-mediated formation of nanotwins and 9R phase in titanium alloys produced by laser powder bed fusion. (February 2023) - Ren, Yaojia; Han, Bo; Wu, Hong; Wang, Jianchuan; Liu, Bin; Wei, Bingqiang; Jiao, Zengbao; Baker, Ian
Abstract: Both nanotwins and 9R phase are rarely form in titanium alloys due to their high stacking fault energy. In this work, we report for first time the formation of nanotwins and 9R phase in ultrafine-grained Ti-5wt.%Cu alloys with an average lath width of 223 nm, which were produced by laser powder bed fusion. Transmission electron microscopy showed that the 9R phase originated from lath boundaries with Cu segregation and terminated at the other boundary of the lath. Besides, deformation resulted in curvature of the lath boundaries and an increase in lath width. This promotes the transition of the central 9R phase to nanotwins, implying that the stabilization of the 9R phase is highly correlated to the width of the laths. This work provides a new route for in situ production of nanotwinned Ti by the laser melting-induced segregation of Cu. Graphical abstract: Image, graphical abstract